2010
DOI: 10.1177/0960327110388533
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol and acetaldehyde disturb TNF-alpha and IL-6 production in cultured astrocytes

Abstract: Ethanol disturbs astroglial growth and differentiation and causes functional alterations. Furthermore, many signalling molecules produced by astrocytes contribute to these processes. The aim of the present study was to investigate the influence of ethanol and its primary metabolite, acetaldehyde, on TNF-alpha and IL-6 production in a rat cortical astrocyte primary culture. We are the first to report that both ethanol and acetaldehyde can modulate TNF-alpha and IL-6 secretion from cultured astrocytes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…The identification of increased expression of Tnf as a direct consequence of ethanol exposure in female but not male astrocytes is intriguing, as TNF alone is capable of inducing neuronal cell death (113,126), but can also be a mechanism to induce an even more potent and damaging inflammatory response (16). Others using unsexed (ie, mixed) astrocyte cultures have found that ethanol exposure reduces TNF concentration following 7 days in culture, which is consistent with downregulation of Tnf in males (105). Interestingly, lactate induces Tnf expression in astroglial cultures, with the trend toward increased lactate in female cultures suggesting one potential mechanism of Tnf induction (6).…”
Section: Figurementioning
confidence: 62%
“…The identification of increased expression of Tnf as a direct consequence of ethanol exposure in female but not male astrocytes is intriguing, as TNF alone is capable of inducing neuronal cell death (113,126), but can also be a mechanism to induce an even more potent and damaging inflammatory response (16). Others using unsexed (ie, mixed) astrocyte cultures have found that ethanol exposure reduces TNF concentration following 7 days in culture, which is consistent with downregulation of Tnf in males (105). Interestingly, lactate induces Tnf expression in astroglial cultures, with the trend toward increased lactate in female cultures suggesting one potential mechanism of Tnf induction (6).…”
Section: Figurementioning
confidence: 62%
“…Ethanol selectively modulates inflammatory signaling of brain astroglia and microglia [52]. For example, ethanol can decrease TNF-a and IL-6 production by astroglia [53].…”
Section: Protective Effects Of Cytokinesmentioning
confidence: 99%
“…It has been implicated as a significant contributor to a broad spectrum of adverse physiological and pathophysiological effects of ethanol (Zimatkin, Pronko et al 2006). Physiological alterations ascribed to acetaldehyde include changes in glial cell function and differentiation (Sarc, Wraber et al 2011). Behavioral alterations include euphoria (intense happiness), anxiolytic (reduced anxiety), hypnotic (also known as sleep time), amnesiac (loss of memory) and aggression, as well as reinforcement or aversion to voluntary ethanol consumption (preference).…”
Section: 3 Acetaldehyde In Ethanol Sensitivity Of the Brainmentioning
confidence: 99%
“…In a study of human brains obtained from smoking and non-smoking alcoholics, increased expression of CYP2E1 protein was found in granular cells of the dentate gyrus and pyramidal cells of the hippocampus (Howard, Miksys et al 2003). Animal studies have found a higher concentration of CYP2E1 protein in astrocytes and glial cells following inflammatory induction (Sarc, Wraber et al 2011). The identification of CYP2E1 in dopaminergic neurons of the substantia nigra suggests that it may be involved in dopamine regulation (Howard, Miksys et al 2003) and have potential implications in Parkinson disease.…”
Section: 5 Cyp2e1 Expression In the Brainmentioning
confidence: 99%